Effects of Physicochemical Variables of Superficial Waters on the Abundance of the North African Freshwater Crab Potamon algeriense (Bott, 1967). (16th March 2021) - Fadlaoui, Soufiane; El Asri, Ouahid; Bouterfas, Mustapha; Melhaoui, Mohammed
Abstract : The large number of pollutants discharged into the aquatic environment may influence the physicochemical and biological qualities of the aquatic ecosystem. This study discloses the global quality of the surface waters and the effect of physicochemical variables on the abundance of the African freshwater crab Potamon algeriense inhabiting Zegzel watercourse, a mountain stream in the northeast of Morocco. Physicochemical variables including streamflow, water temperature, pH, dissolved oxygen, suspended matter, chloride, calcium, magnesium, ammonia, nitrite, nitrate, orthophosphate, and organic matter were evaluated monthly for one year (October 2017–September 2018). The evaluation of the physicochemical quality showed that the waters of all the stations studied are between the excellent and good quality classes concerning all the physicochemical variables and highlights also two variations with a tendency towards degradation, one spatial from upstream to downstream and the other seasonal from the wet to the dry period. The abundance of crabs was recorded to exhibit a positive correlation with dissolved oxygen, calcium ( N = 44) (p < 0.01), and magnesium. However, a negative correlation has been noticed for streamflow ( N = 1) (p < 0.01), water temperature, pH, suspended matter, chloride, ammonia, nitrite, nitrate, orthophosphate, and organic matter. The results obtained reveal that besides the biotic variables, the distribution of P. algeriense also depends on these specific environmental variables.